2017
DOI: 10.15446/acag.v66n4.59753
|View full text |Cite
|
Sign up to set email alerts
|

Detection and sequencing of Potato virus Y (PVY) and Potato leafroll virus (PLRV) in a volunteer plant of Solanum tuberosum L. cv. Diacol-Capiro

Abstract: Viral diseases are among the most limiting factors in the production of potato in Colombia and the rest of the world. The best strategy to control plant viruses consists on the use of certified seed tubers, control of arthropod vectors and the use of adequate crop management practices that reduce mechanical transmission and the presence of viral reservoirs like weeds and volunteer plants. However, the successful implementation of these practices relies on the availability of highly sensitive techniques that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…1. Adopting a suitable diagnostic tool for proper identification (Glais et al, 2017) can be useful in understanding PVY and their characteristic mode of transmission (by various strains), genome organization and protein function, genetic diversity, molecular and bioinformatics aspects of PVY transmission by aphids, methods used in detection and characterization of PVY (Medina Cárdenas et al, 2017), transcriptomics level of response, identification, and monitoring of virus transmission, and vector control strategies in an exclusive manner. 2.…”
Section: Future Prospectivementioning
confidence: 99%
See 1 more Smart Citation
“…1. Adopting a suitable diagnostic tool for proper identification (Glais et al, 2017) can be useful in understanding PVY and their characteristic mode of transmission (by various strains), genome organization and protein function, genetic diversity, molecular and bioinformatics aspects of PVY transmission by aphids, methods used in detection and characterization of PVY (Medina Cárdenas et al, 2017), transcriptomics level of response, identification, and monitoring of virus transmission, and vector control strategies in an exclusive manner. 2.…”
Section: Future Prospectivementioning
confidence: 99%
“…Furthermore, a volunteer plant of potato (cv. Diacol-Capiro) was infected with PVY and the potato leaf roll virus (PLRV) (Medina Cárdenas et al, 2017 ). In this study, researchers observed the effectiveness of RT-PCR (RT-qPCR) and next-generation sequencing (NGS).…”
Section: Genome Organization and Proteinsmentioning
confidence: 99%
“…En los últimos años, se ha aumentado considerablemente la información sobre los virus que afectan diferentes solanáceas cultivadas en Colombia y están disponibles los genomas completos de cepas de las razas PVY O , PVY N y PVY NTN en papa (Villamil-Garzón et al, 2014;Muñoz et al, 2016;Medina et al, 2017;Riascos et al, 2018); de PYVV en papa criolla, tomate (S. lycopersicum) y lulo (S. quitoense) (Villamil-Garzón et al, 2014;Álvarez et al, 2017;Baena et al, 2017;Gallo et al, 2018); así como también de los linajes PVS A y PVS P en papa criolla (Gutiérrez et al, 2012;Vallejo et al, 2016), de PVX en uchuva (Physalis peruviana) y de PLRV en plantas voluntarias de papa (Medina et al, 2017).…”
Section: Introductionunclassified